Prevalence and prognostic significance of malnutrition in patients with acute coronary syndrome treated with percutaneous coronary intervention. Issue 34 (26th August 2022) - Kang, Se Hun; Song, Han Na; Moon, Jae Youn; Kim, Sang-Hoon; Sung, Jung-Hoon; Kim, In Jai; Lim, Sang-Wook; Cha, Dong-Hun; Kim, Won-Jang
Abstract : The incidence and impact of malnutrition on acute coronary syndrome (ACS) remain unclear. This study aimed to evaluate the prevalence, clinical relevance, and prognostic outcomes of malnutrition in patients with ACS treated with percutaneous coronary intervention. This retrospective study included 1930 consecutive patients with ACS undergoing percutaneous coronary intervention and assessed their nutritional status using 3 scoring systems: Controlling Nutritional Status score, nutritional risk index (NRI), and prognostic nutritional index (PNI). The primary endpoint was all-cause mortality. The Controlling Nutritional Status, NRI, and PNI scores showed that 5.2%, 17.5%, and 3.9% of patients were moderately or severely malnourished, respectively. During a median follow-up of 67.2 months (interquartile range: 46.8–88.5 months), 74 (3.8%) patients died. Malnutrition was associated with a significantly increased risk for all-cause mortality compared with good nutrition (adjusted hazard ratios for moderate and severe malnutrition, respectively: 5.65 [95% confidence interval: 3.27–9.78] and 15.26 [7.50–31.05] for the NRI score, 5.53 [2.10–14.49] and 11.08 [5.69–21.59] for the PNI; P < .001). The current findings demonstrated that malnutrition is prevalent among patients with ACS and is closely associated with increased mortality. Further study is needed to evaluate the effects of nutritional interventions on the outcomes of patients with ACS.